Malnutrition Is Highly Prevalent in Patients With Chronic Pancreatitis and Characterized by Loss of Skeletal Muscle Mass but Absence of Impaired Physical Function - Wiese, Mats L.; Gärtner, Simone; von Essen, Nele; Doller, Julia; Frost, Fabian; Tran, Quang Trung; Weiss, Frank Ulrich; Meyer, Fatuma; Valentini, Luzia; Garbe, Leif-A.; Metges, Cornelia C.; Bannert, Karen; et al. (Frontiers in Nutrition, 2022)
Background/Aims: Patients with chronic pancreatitis (CP) have an increased risk of malnutrition, a condition linked to reduced muscle mass and physical performance. We have investigated the risk factors, phenotypic presentation, and health implications associated with malnutrition in CP. Methods: In a multicenter cross-sectional study we recruited patients with confirmed CP and healthy volunteers as a control group. Malnutrition was diagnosed according to the criteria proposed by the Global Leadership Initiative on Malnutrition. We performed detailed examinations of body composition and physical function as well as testing of routine blood parameters and markers of inflammation. Results: We included 66 patients (mean (±SD) age: 56.0 (±14.5) yrs; 51 males) and an equal number of age- and sex-matched controls. Moderate malnutrition was diagnosed in 21% (n=14) and severe malnutrition in 42% (n=28) of patients. Besides weight loss malnourished patients showed lower fat and skeletal muscle mass compared to both non-malnourished subjects and healthy controls. Only in severe malnutrition, blood parameters reflected elevated inflammation and reduced muscle reserves. Handgrip strength in patients did not differ by nutritional status but there was a significant correlation (rho=0.705, p<0.001) with skeletal muscle mass. Although 20 patients (30%) had pathologically reduced skeletal muscle mass, only two individuals (3%) had sarcopenia with concomitantly reduced handgrip strength. Conclusion: Malnutrition is a frequent complication of CP characterized by loss of skeletal muscle mass. As this condition becomes evident only at an advanced stage, regular testing for altered body composition is recommended. Suitable biomarkers and the link between loss of muscle mass and physical function require further investigation. Clinical trial registry number: NCT04474743, https://clinicaltrials.gov/ct2/show/NCT04474743